The vicious spiral in Sudden Infant Death Syndrome - Opdal, Siri Hauge; Stray-Pedersen, Arne; Eidahl, Johanna Marie Lundesgaard; Vege, Åshild; Ferrante, Linda; Rognum, Torleiv Ole (Frontiers in Pediatrics, 2025)
Sudden Infant Death Syndrome (SIDS) is the sudden and unexpected death of an otherwise healthy infant less than 1 year of age where the cause of death remains unexplained after a thorough post-mortem investigation and evaluation of the circumstances. Epidemiological, clinical, biochemical, immunological and pathological evidence indicates that three factors must coincide for SIDS to occur: a vulnerable developmental stage of the immune system and central nervous system in the infant, predisposing factors, and external trigger events. This model is referred to as the fatal triangle or triple risk hypothesis. The concept of a vicious spiral in SIDS, starting with the fatal triangle and ending in death, is proposed as a model to understand the death mechanism. The vicious spiral is initiated by a mucosal infection and immune activation in the upper respiratory and digestive tracts, increased production of cytokines, and an overstimulation of the immature and rapidly developing immune system. A second trigger is the prone sleeping position, which may lead to rebreathing and hypercapnia, in addition to intensify the immune stimulation. In susceptible infants, this induces an aberrant cytokine production that affects sleep regulation, induces hyperthermia, and disrupts arousal mechanisms. In turn, this initiates downregulation of respiration and hypoxemia, which is worsened by nicotine. Inefficient autoresuscitation results in severe hypoxia and accumulation of hypoxic markers which, if not prevented by a normally functioning serotonergic network, contribute to a self-amplifying vicious spiral that eventually leads to coma and death. The purpose of this review is to summarize the research that underpins the concept of the vicious spiral.